2014
DOI: 10.1111/bjd.12652
|View full text |Cite
|
Sign up to set email alerts
|

Classification of segmental vitiligo on the trunk

Abstract: Based on our observations we suggest a new classification into six subtypes for segmental vitiligo lesions on the trunk, allowing categorization of the majority of segmental vitiligo patterns on the trunk. This may have important prognostic and diagnostic significance in early developing lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
1
6
1
Order By: Relevance
“…In a recent study on the classification of the truncal SV lesion, authors reported that SV was more frequently seen on the ventral side (85.8%) than the lateral side or the back of the trunk. This was explained by the dorsoventral embryological migration pattern of the melanocyte precursors . In our study, the tendency of the medial location of SV lesions may also be due to this.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In a recent study on the classification of the truncal SV lesion, authors reported that SV was more frequently seen on the ventral side (85.8%) than the lateral side or the back of the trunk. This was explained by the dorsoventral embryological migration pattern of the melanocyte precursors . In our study, the tendency of the medial location of SV lesions may also be due to this.…”
Section: Discussionsupporting
confidence: 51%
“…This was explained by the dorsoventral embryological migration pattern of the melanocyte precursors. 13 In our study, the tendency of the medial location of SV lesions may also be due to this. When analyzing the dermatomal distribution, cervical dermatome was the most commonly involved dermatome in SND versus trigeminal dermatome in patients with SV.…”
Section: Discussionmentioning
confidence: 48%
“…The characteristic distribution patterns of SV suggest a genetically mutated population of melanocytes which is targeted by a cytotoxic cell response. Different patterns of segmental vitiligo in the face and on the trunk have been detected and can easily be recognized in clinical practice (74,75). By comparing different unilateral and localized skin disorders, we found that the SV pattern does not follow a dermatomal distribution but displays a unique distribution pattern that shares the largest similarity with segmental lentiginosis, followed by epidermal naevus verrucosus (76).…”
Section: Evidence Of Somatic Mosaicismmentioning
confidence: 90%
“…The maximum expected boundary for classification was established as a black line by using these vitiligo lesions. Classification was designated through a consensus of five vitiligo experts based on classifications previously suggested for the face 5 and trunk 6 …”
Section: Figurementioning
confidence: 99%